Hegemonic Masculinity in the Novel Ronggeng Dukuh Paruk by Ahmad Tohari - Wardani, Nugraheni Eko; Suwandi, Sarwiji; Ulya, Chafit; Zulianto, Sugit; Setiyoningsih, Titi (Universitas Muhammadiyah Malang, 2023)
The exploration of hegemonic masculinity within the context of sex and gender roles in Indonesian novels is an intriguing subject for analysis. In light of this background, the present research aimed to (1) describe and explain the hegemonic masculinity in the characters of the novel Ronggeng Dukuh Paruk and (2) describe and explain the efforts of the characters in confronting the hegemonic masculinity in the novel Ronggeng Dukuh Paruk. This study adopted a qualitative descriptive research approach involving a content analysis strategy. The primary data source was Ahmad Tohari's novel Ronggeng Dukuh Paruk. Data collection techniques incorporated document analysis using the theory of hegemonic masculinity. Data validity was ensured through theory triangulation based on various theoretical perspectives. Data analysis followed an interactive approach, encompassing data reduction, data display, and conclusion drawing. The research findings are as follows: (1) Hegemonic masculinity in the novel manifests as a cultural imposition of stigmas and limitations on women in the name of culture, evolving into societal consensus. It arises due to the gender roles deeply intertwined with the cultural values dominating society within a patriarchal culture. (2) The characters in the novel are powerless in the face of hegemonic masculinity, encompassing power relations, the presentation of gender roles, and cathexis due to the firm grip of patriarchal culture on the lives of the community in Ronggeng Dukuh Paruk. Hence, struggles to break free from hegemonic masculinity within a patriarchal culture ultimately fail.